Polymer gel electrolytes based on 49% methyl-grafted natural rubber - Kamisan .A.S,; Kudin .T.I.T,; Ali .A.M.M,; Yahya .M.Z.A, (Universiti Kebangsaan Malaysia, 2011)
Polymer gel electrolytes (PGEs) based on 49% methyl-grafted natural rubber (MG49) were first prepared by dissolving ammonium triflate (NH4CF3SO3) in propylene carbonate (PC) by various molar concentrations of NH4CF3SO3 to obtain liquid electrolytes and were characterized by AC electrical impedance spectroscopy (EIS) measurements to study their conducting behaviour. The liquid electrolyte with optimum conductivity (0.7M) was then gelled with MG49 and their conductivity was also studied. The highest conductivity of liquid electrolyte was 3.6×10-3 Scm-1 and 2.9×10-2 Scm-1 for PGEs. The molecular interactions between components of NH4CF3SO3, PC, and MG49 have been observed by ATR-FTIR spectroscopy study. The downshifting of C=O stretching frequency of PC from 1785 cm-1 to 1780 cm-1 and NH4+ band from 1634 cm-1 to 1626 cm-1 that has been obtained by spectroscopic data in addition of NH4CF3SO3 confirmed the complexation occurrence. Interaction between NH4CF3SO3 and MG49 has also been investigated. This study is focused on the interactions between components in the PGE system and relates them with their conducting behavior